2019
DOI: 10.1016/j.earlhumdev.2019.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Predicting text reading skills at age 8 years in children born preterm and at term

Abstract: Background: Children born preterm are at risk for developing reading difficulties and for decrements in other cognitive skills compared to children born at term. Aims: To assess how domains of function, often negatively impacted by preterm birth, predict reading development in children born preterm and at term. Study design: Longitudinal descriptive cohort study. Subjects: Preterm (n=48; gestational age 22-32 weeks, 30 males) and term (n=41, 18 males) participants were assessed at age 6 years on a battery of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 47 publications
(76 reference statements)
3
34
0
1
Order By: Relevance
“…There was a direct effect of syntactic structure comprehension on text comprehension, coinciding with the results found in other studies carried out with PT children (Guarini et al, 2010;Guarini and Sansavini, 2012). Therefore, the ability to understand sentences, which is highly correlated with working memory, logically affects text comprehension, thus confirming that certain linguistic abilities predict reading comprehension in TD (Muter et al, 2004;Swanson et al, 2008;Lervag and Aukrust, 2010;Kieffer, 2012;Durand et al, 2013) and VPT children (Guarini et al, 2010;Guarini and Sansavini, 2012;Borchers et al, 2019). Contrary to expectations, the association between syntactic comprehension and text comprehension was negative.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…There was a direct effect of syntactic structure comprehension on text comprehension, coinciding with the results found in other studies carried out with PT children (Guarini et al, 2010;Guarini and Sansavini, 2012). Therefore, the ability to understand sentences, which is highly correlated with working memory, logically affects text comprehension, thus confirming that certain linguistic abilities predict reading comprehension in TD (Muter et al, 2004;Swanson et al, 2008;Lervag and Aukrust, 2010;Kieffer, 2012;Durand et al, 2013) and VPT children (Guarini et al, 2010;Guarini and Sansavini, 2012;Borchers et al, 2019). Contrary to expectations, the association between syntactic comprehension and text comprehension was negative.…”
Section: Discussionmentioning
confidence: 78%
“…Working memory influenced reading independently of inhibition and shifting. Borchers et al (2019) studied the effect of a series of variables (PA, language, executive function, and non-verbal IQ) assessed at 6 years of age on text reading skills measured at 8 years of age in a group VPT children and a control group of FT children. VPT children had lower scores than FT children on all measures.…”
Section: Reading and Associated Abilities In Preterm Childrenmentioning
confidence: 99%
“…While verbal skills (phonological awareness, language) at age 6 years were associated with reading outcome in both children born PT and FT, non-verbal cognitive skills (executive function, non-verbal IQ) were only associated with reading outcome in children born PT. These findings suggest that children born PT rely on a broader set of cognitive skills to achieve reading proficiency than children born FT (Borchers et al, 2019b). Whether this broader set of cognitive skills may in turn be mediated by a larger network of white matter pathways is an important topic for future research.…”
Section: Discussionmentioning
confidence: 85%
“…Alternatively, children born PT may involve a larger network in which no specific pathway is predominant for reading. In a recent study, we assessed how different domains of cognitive function, often impacted by PT birth, were associated with reading outcome in children born PT relative to children born FT (Borchers et al, 2019b). While verbal skills (phonological awareness, language) at age 6 years were associated with reading outcome in both children born PT and FT, non-verbal cognitive skills (executive function, non-verbal IQ) were only associated with reading outcome in children born PT.…”
Section: Discussionmentioning
confidence: 99%
“… 12 , 14 , 15 These morbidities are wide-ranging and include cognitive and academic difficulties, as well as impairments in behaviour and social functioning, which typically emerge by school-age. 16–20 Although several factors have been linked with these poorer neurodevelopmental outcomes, including GA and birth weight, the underlying contributions of white matter microstructure to cognitive outcomes are not well understood. Previous studies have shown that FA increases in early childhood are primarily driven by increases in neurite density index (NDI), suggesting that axon density plays an important role in the maturation of cognitive functions in young children.…”
Section: Introductionmentioning
confidence: 99%